Preparation Formulation Clay Mask From Butterfly Pea Flower Pollen (Clitoria Ternatea l.) And Yam Powder (Pachyrhizus Erosus l.) As a Natural Antioxidant - Dian Nur Aisyah; Rahmat Hidayat; Bangkit Riska Permata (International Journal of Health Engineering and Technology, 2026)
Antioxidants play an important role in preventing cell damage, primarily through free radical scavenging mechanisms. This study aimed to formulate clay masks based on butterfly pea (Clitoria ternatea L.) and jicama (Pachyrhizus erosus L.) flower powder and to evaluate their physical characteristics. Butterfly pea flowers were used for their anthocyanin and flavonoid content, which act as antioxidants, while jicama was chosen for its vitamin C and flavonoid content. Clay mask formulations were made with varying concentrations of butterfly pea and jicama flower powder. These were then tested for organoleptic properties, homogeneity, pH, drying time, and antioxidant activity. The clay mask results showed good physical properties: a semi-solid texture, and a pH value within the skin-friendly range of 4.5-8.0, indicating no irritation. The homogeneity test confirmed that all formulations were uniform, without lumps or unmixed particles. The drying time of the clay masks ranged from 15.19 to 15.26 minutes, meeting the optimal range of 15-20 minutes. Antioxidant activity, formula 0 has an IC50 of 102.75 µg/mL (moderate activity), formula 1 (10% butterfly pea flowers, 10% jicama) shows strong antioxidant activity with an IC50 of 62.15 µg/mL. Formula 2 (12% butterfly pea flowers, 8% jicama) shows strong antioxidant activity with an IC50 of 53.70 µg/mL. Formula 3 (8% butterfly pea flowers, 12% jicama), with an IC50 of 41.20 µg/mL, so it is classified as very strong.